(untitled) (REMUNOM, 2025)
With the political and administrative decentralization that played a crucial role in the institutional framework of Brazilian federalism, the Municipal Participation Fund (FPM) has become the main source of financing for Brazilian municipalities. This article aimed to examine the degree of dependence of the municipalities in the microregion of Teófilo Otoni on FPM transfers. The findings indicate a higher dependence on FPM revenues in municipalities with smaller populations and historically limited economic activity. The absence of investment and revenue-generation policies in most of Brazil’s interior tends to maintain a high level of dependence of small municipalities on FPM transfers.